Shaykh Ahmad Sirhindi (971/1564-1034/1624) : A Socio-Religious Reformer Of Mughal India - Arshad Islam, Islam (2014)
Shaykh Ahmad Sirhindi,also known as Mujaddid-i alf-i thani, was a well-known Sufi of the Naqshbandi order in 16th-17th century Mughal India.The period during which he lived has been seen by many as a challenging period for the Muslim intelligentsia, in the wake of numerous religious experiments carried out by the Mughal Emperor Akbar (r. 1556-1605). The religious classes, perceiving these experiments as attacks on Islam, tried to find politically pragmatic solutions to deal with the circumstances. Shaykh Ahmad Sirhindialso sensed the danger ahead and tried to instill an intellectual awakening among Muslims. He not only discussed socio-religious and political matters, but also tried to inculcate the Islamic ethos and restore Islamic shariah in everyday lives.He was well versed in Islamic sciences and tasawwuf(Sufism), and as a result of his efforts to awaken Muslims from their political and religious stupor, he came to be known as theRevivalist of the Second Millennium(Mujaddid-i alf-i thani).He attempted to halt the waning of the influence of the Muslim religious classes in India by trying to enact an Islamic renaissance and the implementation of a more orthodox interpretation of Islamic shariahthan that espoused by the Mughal authorities. He had unique ideas for transforming the ruling elite and the society. His thoughts and the politico-religious ideas of renewal (tajdid) and revival of the prophetic tradition (ihya al-sunnah) are found in his Maktubat,Ithbatal-Nubuwah, Radd-i Rawafid and Ma’arif Laduniyah and other writings. This paper examines Shaykh Ahmad Sirhindi’s political and religious thoughts and ideas from his Arabic and Persian writings, including secondary works in Urdu and English. Keywords: Shaykh Ahmad Sirhindi, Mujaddid-i alf-i thani, tajdid, Shariah,Indian political philosophy.